A Glocalised National Narrative: A Siraya-based Discourse In The Tai-gi Puppet Play Blitzkrieg Siraya - Tenn , Nga-i (Penerbit Universiti Sains Malaysia (USM Press), 2014)
Globalisation, which has become a buzzword in current debates, is said to deconstruct and replace nations in "the era of post-nationalism." On the other hand, fear of being inundated with globalism rekindles local consciousness, forging more "imagined communities" that are co-constituted by interlaced local liaisons. As a consequence, nationalism does not fade out, but undergoes a series of transformations. National narratives re-emerge with varied facets and more localised substantiation. Blitzkrieg Siraya, a Tai-gi puppet play marks this new breed of "glocalised national narrative"—a new discourse fermented by both globalism and localism. Debuting in 2010, Blitzkrieg Siraya receives much acclamation. It tells of how descendants of Han immigrants and Siraya, a lowland Austronesian people populating southern Taiwan, transcend mutual animosity and fight together against an evil spirit to defend their homeland. The narrative gives a vivid picture of Siraya's matrifocal culture, challenging Han-dominated ethnic stereotypes and male-centric gender bias. Two other factors distinguish Blitzkrieg Siraya from other Taiwan-made puppet plays. Unlike Taiwan's traditional puppet shows, which are confined to Chinese framework, Blitzkrieg Siraya is based on Taiwan's historical context. Moreover, it is the first Tai-gi puppet play that highlights Sirayans, who were barely mentioned in the Chinese-Han-dominant discourse. Blitzkrieg Siraya re-addresses Taiwan as a multi-ethnic society with solid Austronesian roots.